Uganda : Technical Assistance Report-Fiscal Regimes for Extractive Industries: Next Phase. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses the advice provided by the IMF staff to the authorities of Uganda regarding extractive industry fiscal regimes. As Uganda's portfolio of projects diversifies in the oil sector, the minimum take could be adjusted to allow for possible bonus bids, and for higher shares in the most successful projects. The royalty design also needs to take account of new provisions for distribution of a portion to local governments. The cost recovery limit could be set at 70 percent after deduction of royalty. In addition to work program, either a signature bonus or an upper tier of production sharing should form the bid variable in the licensing round, with all other items fixed and non-negotiable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet